Analytical procedures using SEM/EDX equipment for determining heavy metals contents in fly ash genereated from domestic solid waste incinerators: a casestudy of Soc Son waste to power plant in Ha Noi - Tra Mai, Ngo; Thi Hong, Khuat; Thi Thuy Hang, Nguyen; Thi Ha Lien, Nghiem; Huu Tap, Van; Thi Thanh Hang, Phan; Thi Tham, Trinh; Duc Toan, Vu; Thi Hoa, Nguyen; Hung Son, Nguyen; et al. (Vietnam Journal of Science and Technology, 2024)
The researching and establishing of this process for analyzing fly ash generated from a domestic solid waste treatment plant by Scanning Electron Microscopy Energy Dispersive X-Ray (SEM/EDX) method were investigated. Three sampling series with twelve (12) fly ash samples collected at SocSon waste-to-power plant Ha Noi, Viet Nam were used for: (i) analytical procedure establishment; (ii) standardization; and (iii) test analysis. At each measurement, a cross-check with one random sample using X-ray fluorescence spectroscopy (XRF) method was carried out to verify the accuracy of the SEM/EDX measurements. As a result, a 6-step measurement procedure has been proposed, including: experimental preparation, sample weighting, liquid/solid phase separation, sample drying, sample measurement and data processing. And for procedure adjustment, liquid/solid phase separation was repeated twice while drying time was doubly increased from 24 to 48 hours to collect all heavy metal contaminated residues. The proposed procedure could provide results in about 3-5 seconds without any requirement of sample digestion while most of the heavy metalspresent in fly ash, including low-content ones such as Ag, Cd and Cr were simultaneously displayed. The standardized measurement procedure was applied to test the hazardous properties of fly ash by comparing with Technical regulations (QCVN) 07:2009/BTNMT – National Technical Regulations on Hazardous waste thresholds. The results identified that fly ash could be primarily considered as hazardous waste with 5/14 heavy metal parameters exceed the limit from 1.7 to 9.5 times and needs to be collected and treated properly. This result is also quite similar to the studies that have been done in China, the US or Viet Nam. Thus, SEM/EDX method could be used for analyzing heavy metal components in fly ash samples of solid waste treatment plants.